Biblical Intertextual Strategies in “The Study Quran: A New Translation and Commentary”—An Analysis of Presentation Forms in Contemporary Qur’anic Exegesis - Andesra, Aan; Yulianda, Reno (UIN Sultan Syarif Kasim Riau, 2025)
Cross-scriptural exegesis, a classical yet not fully normalized practice, has become central to contemporary Qur’anic studies. Seyyed Hossein Nasr et al.’s The Study Quran: A New Translation and Commentary exemplifies this shift by creating intertextual dialogue across scriptures to emphasize narrative and theological continuity. This study examines how the Bible in The Study Quran especially regarding Qur’an 12:23–42, which covers feminine temptation and the prisoners’ dreams is presented not just narratively but through a systematic, scholarly approach. The researcher applies Julia Kristeva’s theory of intertextuality and Mikhail Bakhtin’s dialogic theory (heteroglossia and carnivalesque), using a qualitative-textual method based on library sources. The findings reveal that intertextuality in the verses encompasses narrative (Q. 12:23–35, 36–42), legal (Q. 12:25, 36), and semiotic (Q. 12:36, 41) dimensions. The intertextual models include references (Q. 12:36), explanations (Q. 12:23), comparisons (Q. 12:23, 25, 35–38, 41, 42), and critiques (Q. 12:37–40). These forms create an analytical-comparative work aligned with its dialogical purpose, while upholding the Qur’an’s hierarchical authority over the Bible within a theological framework. From a dialogic view, the multiple voices the Qur’an (proton), the exegete (neutron), and the Bible (electron) reflect a carnivalesque dynamic. Abstrak: Fenomena tafsir lintas kitab merupakan praktik klasik yang belum sepenuhnya dinormalisasikan, tetapi kini menjadi jantung diskursus studi al-Qur’an kontemporer. Karya Seyyed Hossein Nasr dkk., The Study Quran: A New Translation and Commentary, merefleksikan pergeseran ini dengan membangun dialog intertekstual lintas kitab guna menyoroti kesinambungan naratif dan teologis. Penelitian ini bertujuan menelaah bagaimana Bibel dalam The Study Quran, khususnya pada QS. Yūsuf: 23–42 yang berkaitan dengan kisah godaan perempuan dan tafsir mimpi narapidana tidak sekadar dikutip secara naratif, tetapi dihadirkan melalui strategi ilmiah yang sistematis. Dalam konteks ini, peneliti menggunakan teori intertekstualitas Julia Kristeva (intrinsik) dan teori dialogis Mikhail Bakhtin (heteroglossia dan carnivalesque). Adapun metode yang digunakan ialah kualitatif-tekstual dengan memanfaatkan sumber-sumber kepustakaan. Hasil penelitian menunjukkan bahwa ragam bentuk interteks terkait tema ayat memuat kisah (QS. Yūsuf: 23-35 dan 36-42), hukum (QS. Yūsuf: 25 dan 36), dan semiotik (QS. Yūsuf: 36 dan 41). Terkait model intertekstual memuat rujukan (QS. Yūsuf: 36), penjelasan (QS. Yūsuf: 23), perbandingan (QS. Yūsuf: 23, 25, 35, 36, 37, 38, 41, dan 42), dan kritik (QS. Yūsuf: 37-40). Ragam bentuk interteks tersebut menjadikannya sebagai bentuk yang bersifat analitis-komparatif, hal ini senada dengan tujuan pengaplikasian dalam rangka membangun dialog, walau dalam konsep teologi tetap memuat hirarki otentisitas al-Qur’ān dibanding Bibel. Jika dilihat dalam kacamata dialogis menunjukkan keberagaman bentuk suara proton (al-Qur’ān), suara neutron (mufasir), dan suara elektron (Bibel) dapat menggambarkan karnivalistik.